Phase‐contrast MRI with hybrid one and two‐sided flow‐encoding and velocity spectrum separation. Issue 1 (9th August 2016) - Wang, Da; Shao, Jiaxin; Ennis, Daniel B.; Hu, Peng
Abstract : Purpose: To develop and evaluate a phase‐contrast MRI (PC‐MRI) technique with hybrid one and two‐sided flow‐encoding and velocity spectrum separation (HOTSPA) for accelerated blood flow and velocity measurement. Methods: In the HOTSPA technique, the two‐sided flow encoding (FE) is used for two FE directions and one‐sided is used for the remaining FE direction. Such a temporal modulation of the FE strategy allows for separations of the Fourier velocity spectrum into components for the flow‐compensated and the three‐directional velocity waveforms, accelerating PC‐MRI by encoding three‐directional velocities using only two repetition times (TRs) instead of four TRs as in standard PC‐MRI. The HOTSPA was evaluated and compared with standard PC‐MRI in the common carotid arteries of six healthy volunteers. Results: Total volumetric flow and peak velocity measurements based on HOTSPA and the conventional PC‐MRI were in good agreement with a bias of − 0.005 mL (−0.1% relative bias error) for total volumetric flow and 1.21 cm/s (1.1% relative bias error) for peak velocity, although the total acquisition time was 50% of the conventional PC‐MRI. Conclusion: The proposed HOTSPA technique achieved nearly two‐fold acceleration of PC‐MRI while maintaining accuracy for total volumetric flow and peak velocity quantification by separating the paired acquisitions in the Fourier velocity spectrum domain. Magn Reson Med 78:182–192, 2017. © 2016 International Society for Magnetic Resonance in Medicine